Pug's road trip ebook A branches book. - May, Kyla (Diary of a Pug, 2022)
A seventh Branches early chapter book featuring everyone's favorite pug, Bub, and his human, Bella! Pick a book. Grow a Reader! This series is part of Scholastic's early chapter book line, Branches, aimed at newly independent readers. With easy-to-read text, high-interest content, fast-paced plots, and illustrations on every page, these books will boost reading confidence and stamina. Branches books help readers grow! Bub the pug; his human, Bella; and their friend Jack are excited to go on a road trip. There will be so much to see and do! But when Jack can no longer come, Bella and Bub vow to bring him something special from their trip. Can Bub and Bella find the perfect souvenir for Jack? With full-color artwork throughout, this funny and charming diary-format early chapter book is perfect for anyone who believes a furry pal is the best kind of friend.